Travel Intention of Muslim Tourist to Visit Non-Muslim Country: A Conceptual Paper of Extended Theory of Planned Behavior (ETPB) - Noveri Maulana; Mardiansah Subhani (International Journal of Islamic Business and Economics (IJIBEC), 2021)
The purpose of this paper is to analyze the literatures on Muslim behavior toward purchasing the halal tourism using the Theory of Planned Behavior (TPB). This paper is analyzing literature which indexed in the Scopus indexed publication during 2010-2020. Keyword ‘Halal Tourism’ and ‘Theory of Planned Behavior’ is used in the searching process. There are fifteen paper which suitable with the keywords and proceed to the further analysis using Integrative literature review. Result analysis proposes several topics for future research regarding the role of religiosity in understanding Muslim purchase intention toward halal tourism, the expanded model of TPB which considering the destination image and materialism, and also the research topic on determining halal factors in the certification standard of halal tourism services among tourism practitioners. Hence, future research agenda is also discussed as the follow up study of this conceptual paper.